Perjanjian Jaminan Fidusia Kaitan dengan Penyidikan Tindak Pidana Perlindungan Konsumen - Sipayung, Iskandar Muda; Kamello, Tan; Marlina, Marlina; Kartika, Arie (Universitas Medan Area, 2019)
This research is normative legal research, an explanatory descriptive nature that aims to describe, disclose and explain the relationship between the non-criminal investigation of consumer protection with consumer guarantee agreements. The analysis is carried out using a juridical approach method which is then synchronized vertically or horizontally to related laws to see the existence of harmonization and certainty in the existing legal system. To further sharpen the results of the study also carried out an analysis of the effectiveness of the case. The results of the study provide an illustration that the Fiduciary Security Act has a problem in Article 15 regarding the provisions of the procedure for execution that is contrary to the HIR / RBg. Likewise, between Article 54 paragraph (3) and Article 56 paragraph (2) of the Consumer Protection Act, an inconsistency occurs in its application and implementation. With respect to agreements containing standard clauses, business actors and / or their management can be criminalized, in accordance with Article 18 in conjunction with Article 62 of the Consumer Protection Act. It is recommended that the Government and the House of Representatives of the Republic of Indonesia be able to revise these articles in order to realize legal certainty for all parties.